MICROCONTROLLER-BASED LINE FOLLOWER ROBOT FOR AUTOMATED AGRICULTURAL GOODS TRANSPORTATION SYSTEM - Milda Yuliza; Herizon; Fisla Wirda; Putri Ardila; Rahmat (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
As technological advancement continues to accelerate, automation-based solutions have become increasingly relevant for implementation in the Indonesian agricultural sector. One manifestation of this technological progress is the utilization of robotic systems to support various agricultural activities. This research aims to design and develop a microcontroller-based line follower robot capable of automatically following designated paths to facilitate the transportation of tomato harvests in agricultural areas. The study employs an experimental approach encompassing hardware design, electronic circuit design, software programming, and mechanical assembly. The robot integrates a five-sensor TCRT5000 infrared array for line tracking navigation and a TCS3200 color sensor for tomato classification based on ripeness indicators. Testing results demonstrated that temporal variations on the red and yellow paths were influenced by braking maneuver differences, sensor color response characteristics, and motor speed during turning operations. From fifteen color sensor trials, the system achieved 66.6% accuracy with ten correct detections and five misclassifications. The combination of five line sensors (S0 to S4) successfully determined directional movement, functioning as the primary navigation system in conjunction with the color sensor for routing decisions at intersections. Testing of the L298N motor driver confirmed effective wheel control, producing straight-line motion, left and right pivot rotations, and complete stops according to programmed motor input combinations. The developed system demonstrates the feasibility of integrating line-following navigation with color-based classification for automated post-harvest transportation in agricultural settings.